Use of Haemate® P as immune tolerance induction in patients with severe haemophilia A who failed previous induction attempts: a multicentre observational study. (8th October 2012) - Rothschild, C.; D'oiron, R.; Borel‐derlon, A.; Gruel, Y.; Navarro, R.; Negrier, C.
Summary Immune tolerance induction (ITI) can eliminate factor VIII (FVIII) inhibitory antibodies that appear during FVIII replacement therapy. If first‐line ITI fails, switching to a different FVIII concentrate, especially one containing von Willebrand factor (VWF), has been advocated. The objective of the study was to assess the efficacy and safety of Haemate® P, a plasma‐derived FVIII concentrate containing high levels of VWF, as ITI in severe haemophilia A patients who had failed at least one prior ITI attempt with a different FVIII concentrate. In this multicentre, observational study, Haemate® P was administered at a starting dose of 83–308 IU kg−1 day−1 (1500–6000 IU day−1). Efficacy was assessed by standard criteria (e.g. Bethesda titre, FVIII recovery and half‐life), and bleeding characteristics. Nine patients from six haemophilia centres were treated with Haemate® P after failing one (n = 2), two (n = 5) or three (n = 2) prior ITI courses. The median time from inhibitor detection to Haemate® P treatment was 5.4 years. The median Haemate® P dose was 134 IU kg−1, and the median treatment duration 32 months. During median of 47 months of follow‐up, complete response, partial response and treatment failure were observed in one, three and five patients respectively. Five patients experienced seven adverse events (AEs), including two serious AEs (sepsis). Haemate® P was discontinued due to an AE in one patient with a partial response. Haemate® P salvage ITI resulted in complete or partial tolerization in four of nine patients (44%) who had failed previous ITI attempts using different FVIII concentrates.